Observation of tau -lepton decay to five charged particles. - Beltrami, I; Bylsma, BG; DeBonte, R; Gan, K; Koltick, D; Loeffler, F; Low, E; McIlwain, R; Miller, D; Ng, C; Ong, P; Rangan, L; et al. (1985)
The production of lepton pairs in e+e- collisions at 29 GeV has been used to study the inclusive decay into five charged particles. Ten events are observed in the high-resolution spectrometer giving a branching ratio of B(5+n+)=(1.30.4)×10-3. Five of the events contain photons which are consistent with coming from a single 0. With this interpretation we measure B(5), B(50)=(6.73.0)×10-4. The branching-ratio upper limit for the decay mode K0+3 is found, at 90% confidence level, to be 2.7×10-3. © 1985 The American Physical Society.